Application of The Role Playing Method in Learning Drama Texts to Improve Writing Skills for Class VIII Junior High School Students - Ai Siti Atikah; Rochmat Tri Sudrajat; Ika Mustika (IKIP Siliwangi, 2023)
The ability to write drama texts at the junior high school level is still relatively low. This study aims to improve the ability to write drama texts by using the role playing method. The research subjects were 35 students of class VIII at SMPN 2 Bandung in the academic year 2020/2021.This research was conducted using a qualitative descriptive research method. In collecting data, the researcher used test, observation and interview instruments. Before and after the learning treatment, students were given a pretest and posttest. Based on the results of the research conducted, the scores for writing drama texts were obtained with an average pretest of 55.4 and posttest of 81.7. The results of the SPSS analysis showed a significance of 0.000<0.05 so that there was a difference between the learning outcomes before and after the treatment. The results obtained indicate that the application of the role playing method in learning to write drama texts can be increased by a difference of 26.3 in grade VIII junior high school students.